Precise AuxPt1−x alloy nanoparticle array of tunable composition for catalytic applications - Jahn, Sarah Renate; Lechner, Sebastian James; Freichels, Helene; Möller, Martin; Spatz, Joachim P. (Scientific reports, 2016)
A 3-dimensional Block Copolymer Micellar nanoLithography (BCML) process was used to prepare AuxPt1−x alloy nanoparticles (NPs) monodisperse in size and composition, strongly anchored onto SiO2-particles (0.2 wt.% AuxPt1−x/SiO2). The particles possess a face-centered cubic (fcc) crystal structure and their size could be varied from 3-12 nm. We demonstrate the uniformity of the Au/Pt composition by analyzing individual NPs by energy-dispersive X-ray spectroscopy. The strongly bound AuxPt1−x NPs catalyzed the oxidation of CO with high activity. Thermal ageing experiments in pure CO2 as well as in ambient atmosphere demonstrated stability of the size distribution for times as long as 22 h.
Im Titel sind x und 1-x tiefgestellt
Gesehen am 30.04.2020